2003
DOI: 10.1176/appi.ajp.160.1.178
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the Mood Disorder Questionnaire: A General Population Study

Abstract: The Mood Disorder Questionnaire is a useful screening instrument for bipolar I and II disorders in the community. The operating characteristics of the Mood Disorder Questionnaire in the general population differ substantially from its characteristics in outpatient psychiatric settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
187
5
11

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 261 publications
(217 citation statements)
references
References 2 publications
9
187
5
11
Order By: Relevance
“…11,20,[22][23][24] It was comparable to other instruments such as the MDQ. 26,29 This reliability is similar to values found in samples of remitted patients (Italy, Spain, and Sweden) 11,20 and also in the general population (Germany and Sweden). 33 This indicates stable psychometric properties, regardless of clinical status or cultural differences.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…11,20,[22][23][24] It was comparable to other instruments such as the MDQ. 26,29 This reliability is similar to values found in samples of remitted patients (Italy, Spain, and Sweden) 11,20 and also in the general population (Germany and Sweden). 33 This indicates stable psychometric properties, regardless of clinical status or cultural differences.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, we contrasted the HCL-32 VB with the Mood Disorder Questionnaire (MDQ), a screening instrument largely used for improving the identification of BD. 26 Its English version was shown to have a sensitivity of 73% and a specificity of 90% for a sample consisting mostly of BD-I patients. In the development study, the MDQ was more efficient in identifying BD-I than BD-II.…”
Section: Introductionmentioning
confidence: 99%
“…'; Hirschfeld et al, 2000). Originally designed and validated for use in outpatient populations, the MDQ has since been validated in the general population (specificity ¼ 0.97; Hirschfeld et al, 2003), and has been used to define the common bipolar phenotype in terms of elevated mood in young people (Rock et al, 2010). Specifically, two participant groups were recruited: participants with MDQ scores ¼ 0 (control participants), and participants with MDQ scoresX7 (BPP).…”
Section: Participants and Recruitmentmentioning
confidence: 99%
“…At the original cut-off of seven items, its sensitivity was higher than the English version for detecting SCID diagnosis of bipolar disorder in the community (28.1%) (Hirschfeld et al, 2003), but its specificity was lower. It also demonstrated a higher sensitivity than in a previous community study that, with regard to DSM-IV bipolar disorder, found the MDQ to have zero sensitivity (0) and high specificity (0.95) (Chung et al, 2009).…”
Section: Discussionmentioning
confidence: 82%